NUMERICAL MODELLING TO CREATE GROUND REACTION CURVE ON NON-CIRCULAR CROSS SECTION TUNNEL - Felix Dante Wiguna Hamzah, Ben
Mining tunnel or civil tunnel excavation will cause tunnel internal support pressure to decrease. From the ground reaction curve, a decrease in tunnel internal support pressure will cause an increase in wall tunnel displacement. The author of this study will compare the result between numerical finite element method and analytical for non-circular tunnel. In this case, the tunnel will be modeled in the shape of a square and horseshoe. The side rock characteristic is homogenous, continuous, isotropy and elastoplastic with specific gravity equal to 0.027 MN/m3. Three main pressures of the tunnels have the same value equal to 7 MPa which is the internal support pressure itself at zero advance. The comparison result states that there are differences between the numerical and analytical ground reaction curve on non-circular tunnels. The difference is in the tunnel internal support critical pressure (Pcr). Square shaped tunnel Pcr value equal to 2.1 MPa while equivalent circular shaped tunnel equal to 2.88 MPa and horseshoe shaped tunnel Pcr value equal to 2.45 MPa while equivalent circular shaped tunnel equal to 2.88 MPa.